Analysis of International Mergers and Acquisitions in the Pharmaceutical Industry - Božo Matić; Vlatka Bilas; Vedran Bači (Ekonomski Vjesnik, 2011)
There are numerous researches which analyze mergers and acquisitions, but most of them do not focus on a certain industry, but their sample considers companies from different industries. This paper focuses on mergers and acquisitions in the pharmaceutical industry. It is assumed that pharmaceutical companies with no experience in mergers and acquisitions achieve better results in relatively small and domestic mergers and acquisitions while pharmaceutical companies with greater experience in mergers and acquisitions are successful even in bigger and international mergers and acquisitions. Bigger mergers and acquisitions and international mergers and acquisitions are more risky for the companies so lack of experience in mergers and acquisitions additionally increases risks during the process of mergers and acquisitions. On average, such increase of the risk results in lower returns for stock owners of pharmaceutical companies.